Gorilla is scared but learns to be brave - Brooke, Jasmine; Bailey, Emma; Rush, Jenny (Leicester, England Fox Eye publishing, 2022)
This book helps children explore difficult feelings and how to manage them, it includes discussion activities for adults to use with children to help them further examine the thoughts, feelings and behaviours featured in the book
English stories
Keywords: English stories